SURVEY OF THE PURCHASING POWER OF HOUSEHOLDS CONCERNING CERTAIN MILK PRODUCTS - Delyana DIMOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The information about the food products has been organized in a created relational database. It has been extracted from the web site of the Bulgarian National Statistical Institute. The paper surveys the purchasing power of households concerning certain milk products (milk, yoghurt, white cheese and yellow cheese) in Bulgaria for the period 2005-2019. These data are searched from the database tables. Subsequently, they have been processed and analyzed. The percentage change in the purchasing power of households concerning each product for current year in comparison with the previous year has also been calculated. The results showed that a process of almost continuous decrease of the purchasing power of households concerning milk was observed for 2007-2011. A gradual growth of this indicator is obtained during 2012-2019. Approximately the same dependences were established for the purchasing power of households concerning yoghurt in the considered period. An increasing tendency of the studied indicator for the white cheese was observed in the interval 2015-2019. A similar situation is obtained for the purchasing power of households concerning yellow cheese for 2012-2019.